Protective Effect of Bangle (Zingiber cassumunar ROXB) Rhizome Extract on CCl4-Induced Liver Damage of Rats - Elmeizy Arafah; Deddy Muchtadi; Fransiska R Zakaria; Tutik Wresdiyati; Sidik . (Jurnal Teknologi dan Industri Pangan, 2004)
Zingiber cassumunar Roxb known as Bangle, has antioxidative and antiinflammatory activities. It has been used for medicinal purposes traditionally. The aim of this study was to investigate whether administration of Z. cassumunar extracts orally may prevent acute liver damage induced by carbontetrachloride (CCl4) in rats. The study was carried out on 5 groups of male Sprague-Dawley rats (n=5). Group 1 was given ethyl acetate fraction of Bangle rhizome extract (30 mg/kg bw) (KS), group 2 was given dry juice of Bangle rhizome (30 mg/kg bw) (SK), group 3 was given curcuminoid (30 mg/kg bw) (KUR), group 4 as negative control (KN) given 5% Tween 80 solution (10 ml/kg bw) and Group 5 as control (K). Carbontetrachloride 0,1 ml/kg bw was given orally after 7 days to group KS, SK, KUR and KN. Rats were terminated 24 hours after CCl4-induction. Liver injury was evaluated by analyzed SGPT and SGOT activities from the serum and histopathologycal examination was conducted on the liver. The results clearly indicated that extracts of Z. cassumunar could reduced significantly the degree of liver damage induced by CCl4. It may be concluded that Z. cassumunar rhizome could be used as substance for hepatoprotector. Key words : Zingiber cassumunar, hepatoprotector, Liver damage.